Pendidikan Kesehatan tentang Menstruasi terhadap Kesiapan dalam Menghadapi Menarche pada Siswi Kelas V dan VI - Mera Delima; Yessi Andriani; Tri Lestari (Jurnal Kesmas Asclepius, 2020)
This study aims to determine health education's effect on menstruation on readiness to face menarche in grade V and VI students at SDN 39 Kinali in 2019. The research method is pre-experimental quantitative research with a one-group pretest-posttest design. The results of this study are the readiness of respondents to face menarche before being given health education is 91.50, after being given health education is 101.25 the mean difference between the respondent's willingness to meet menarche before and after health education with statistical test results obtained in P = 0.001 with a difference in mean Average 9750. In conclusion, health education has an effect on menstruation on students' readiness to face menarche. Keywords: Menarche, Menstruation, Health Education